Hexa Histidine–Tagged Recombinant Human Cytoglobin Deactivates Hepatic Stellate Cells and Inhibits Liver Fibrosis by Scavenging Reactive Oxygen Species. Issue 6 (22nd May 2021) - Dat, Ninh Quoc; Thuy, Le Thi Thanh; Hieu, Vu Ngoc; Hai, Hoang; Hoang, Dinh Viet; Thi Thanh Hai, Nguyen; Thuy, Tuong Thi Van; Komiya, Tohru; Rombouts, Krista; Dong, Minh Phuong; Hanh, Ngo Vinh; Hoang, Truong Huu; et al.
Abstract : Background and Aims: Antifibrotic therapy remains an unmet medical need in human chronic liver disease. We report the antifibrotic properties of cytoglobin (CYGB), a respiratory protein expressed in hepatic stellate cells (HSCs), the main cell type involved in liver fibrosis. Approach and Results: Cygb ‐deficient mice that had bile duct ligation–induced liver cholestasis or choline‐deficient amino acid–defined diet–induced steatohepatitis significantly exacerbated liver damage, fibrosis, and reactive oxygen species (ROS) formation. All of these manifestations were attenuated in Cygb ‐overexpressing mice. We produced hexa histidine–tagged recombinant human CYGB (His‐CYGB), traced its biodistribution, and assessed its function in HSCs or in mice with advanced liver cirrhosis using thioacetamide (TAA) or 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC). In cultured HSCs, extracellular His‐CYGB was endocytosed and accumulated in endosomes through a clathrin‐mediated pathway. His‐CYGB significantly impeded ROS formation spontaneously or in the presence of ROS inducers in HSCs, thus leading to the attenuation of collagen type 1 alpha 1 production and α‐smooth muscle actin expression. Replacement the iron center of the heme group with cobalt nullified the effect of His‐CYGB. In addition, His‐CYGB induced interferon‐β secretion by HSCs that partly contributed to its antifibrotic function. Momelotinib incompletely reversed the effect of His‐CYGB. Intravenously injected His‐CYGB markedly suppressed liver inflammation, fibrosis, and oxidative cell damage in mice administered TAA or DDC mice without adverse effects. RNA‐sequencing analysis revealed the down‐regulation of inflammation‐ and fibrosis‐related genes and the up‐regulation of antioxidant genes in both cell culture and liver tissues. The injected His‐CYGB predominantly localized to HSCs but not to macrophages, suggesting specific targeting effects. His‐CYGB exhibited no toxicity in chimeric mice with humanized livers. Conclusions: His‐CYGB could have antifibrotic clinical applications for human chronic liver diseases.